Occupational Medicine Expert Witness Cooperating with Lawyers in Launch of a Proposal of Law Amendment on Compulsory Health Insurance Based on the Hairdresser Allergic Dermatitis – Case Report - Lalić, Hrvoje (Open Access Macedonian Journal of Medical Sciences, 2024)
BACKGROUND: Hairdressers, barbers, beauticians, nail beauticians and cleaners are the most common occupations where work-related skin diseases occur. The aim of this paper is to present the role of an Occupational Medicine Specialist who was given the task of evaluating whether the hairdresser's illness is in a cause-and-effect relationship with the employer - the plaintiff, and whether the hairdresser has a predisposition to the onset of the disease. CASE PRESENTATION: This paper presents the case of a 24-year-old hairdresser who developed allergic contact dermatitis. Her employer sued the Croatian Health Insurance Institute, holding that she has no financial obligations towards her employee, whom she had dismissed, because she was not to blame for the onset of her contact dermatitis. The specialist in occupational medicine confirmed the opinion of institutional expert bodies that this case is an occupational disease according to the Law on Compulsory Health Insurance. However, the employer is partially right, because she gave her the necessary protective equipment and supplied her with permitted chemicals, and it is not her fault that her employee developed allergic dermatitis due to her tendency to the said disease, and she believes that she should not be paid 100% compensation during sick leave. This is a rare case where everyone is right. CONCLUSION: Therefore, to solve the case fairly, it is necessary to make an addition to the Law, to reject allergic occupational dermatitis as an occupational disease, in case it is an innate tendency of the organism with a late response to occupational allergens. The employer would be freed from the financial burden of payment, which obligation would be assumed by the HZZO, which would refer the patient to professional rehabilitation in the sense of retraining for another job.